Orbitofrontal neurons signal sensory associations underlying model-based inference in a sensory preconditioning task - Brian F Sadacca; Heather M Wied; Nina Lopatina; Gurpreet K Saini; Daniel Nemirovsky; Geoffrey Schoenbaum (eLife, 2018)
Using knowledge of the structure of the world to infer value is at the heart of model-based reasoning and relies on a circuit that includes the orbitofrontal cortex (OFC). Some accounts link this to the representation of biological significance or value by neurons in OFC, while other models focus on the representation of associative structure or cognitive maps. Here we tested between these accounts by recording OFC neurons in rats during an OFC-dependent sensory preconditioning task. We found that while OFC neurons were strongly driven by biological significance or reward predictions at the end of training, they also showed clear evidence of acquiring the incidental stimulus-stimulus pairings in the preconditioning phase, prior to reward training. These results support a role for OFC in representing associative structure, independent of value.